2016
DOI: 10.1128/iai.00312-16
|View full text |Cite
|
Sign up to set email alerts
|

Secretion Chaperones PrsA2 and HtrA Are Required for Listeria monocytogenes Replication following Intracellular Induction of Virulence Factor Secretion

Abstract: The Gram-positive bacterium Listeria monocytogenes transitions from an environmental organism to an intracellular pathogen following its ingestion by susceptible mammalian hosts. Bacterial replication within the cytosol of infected cells requires activation of the central virulence regulator PrfA followed by a PrfA-dependent induction of secreted virulence factors. The PrfA-induced secreted chaperone PrsA2 and the chaperone/protease HtrA contribute to the folding and stability of select proteins translocated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…PrsA2 is responsible for folding and stabilization of virulence proteins while HtrA folds but also degrades misfolded proteins to avoid toxic protein accumulation at the membrane cell wall interface. Therefore, in parallel with our data, L. monocytogenes ΔprsA2 ΔhtrA mutants have previously been shown to be defective for bacterial replication within J774 cells [41]. According to Brockstedt et al [42], the attenuated vaccine strains have a reduced capacity for infecting the nonphagocytic cells, which contributes to its safety.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PrsA2 is responsible for folding and stabilization of virulence proteins while HtrA folds but also degrades misfolded proteins to avoid toxic protein accumulation at the membrane cell wall interface. Therefore, in parallel with our data, L. monocytogenes ΔprsA2 ΔhtrA mutants have previously been shown to be defective for bacterial replication within J774 cells [41]. According to Brockstedt et al [42], the attenuated vaccine strains have a reduced capacity for infecting the nonphagocytic cells, which contributes to its safety.…”
Section: Discussionsupporting
confidence: 85%
“…ALYAA FAROUK HESSIN et al The safety of living vaccine vectors is always a primary concern, yet chosen vectors must still be capable of stimulating host immunity while not themselves presenting a danger for the host. The L. monocytogenes double secretion chaperone mutant ΔprsA2 ΔhtrA represents a safe, effective delivery vehicle with limited risk associated with infection [41]. Both chaperones have pivotal roles in maintaining survival of L. monocytogenes within the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, its chaperone function mainly promotes folding and assembly of unfolded proteins, whereas the protease function removes misfolded proteins to prevent their toxic accumulation [22]. In the foodborne pathogen L. monocytogenes similar functions have been suggested since several research groups reported that the expression of HtrA in L. monocytogenes represents a significant contribution to bacterial growth and survival under stress conditions and to in vivo pathogenesis [58]. However, the expression and protease activity of listerial HtrA has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a L. monocytogenes ΔhtrA deletion mutant showed a severe defect in biofilm formation and an attenuated virulence in mice [7]. A recent study suggested a putative function of HtrA in listerial replication in infected host cells and underlined the importance of HtrA for tolerating the changing environment in the infection process [8].…”
Section: Introductionmentioning
confidence: 99%
“…New facets of its properties have recently been revealed ( Figure 2 ). PrfA was shown to induce secretion of the chaperone PrsA2 and the chaperone/protease HtrA, whose protein folding and stabilizing functions promote bacterial fitness and survival during infection of macrophages (Ahmed and Freitag, 2016 ). In addition, PrfA function has been reported to depend on the balance between activating and inhibitory oligopeptides imported by the Opp permease (Krypotou et al, 2019 ).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%